2019
DOI: 10.1186/s12913-019-3963-y
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by caregivers of virally non-suppressed children on the intensive adherence counselling program in Uganda: a qualitative study

Abstract: Background Of the estimated 130,000 children living with HIV in Uganda, 47% are receiving ART. Only 39.3% have suppressed HIV-1 viral load to levels below 50 copies per ml. Caregivers are key drivers of adherence to achieve viral suppression in children. We investigated the challenges and potential support required by caregivers of ART-treated children. Methods A qualitative study was conducted within the Infectious Diseases Institute paediatric ART program in Kampala a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 32 publications
3
46
0
Order By: Relevance
“…Participants in this study reported that the cessation of the ‘mentor mother’ pediatric adherence support mechanism at case-study facilities had contributed to declining viral suppression among pediatric patients. Studies in Uganda suggest that viral suppression among pediatric patients is as low at 23% [ 29 ] and with the loss of tailored programs for pediatric patients, it is possible that even greater challenges to viral suppression among this group may be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in this study reported that the cessation of the ‘mentor mother’ pediatric adherence support mechanism at case-study facilities had contributed to declining viral suppression among pediatric patients. Studies in Uganda suggest that viral suppression among pediatric patients is as low at 23% [ 29 ] and with the loss of tailored programs for pediatric patients, it is possible that even greater challenges to viral suppression among this group may be seen.…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, regular VL monitoring is done at the Central Public Health Laboratory through the districts’ laboratory hubs and in case of virological non-suppression, that is; two consecutive viral loads above 1000 copies/ml done at least 3–6 months apart [ 8 ], 3 sessions of intensive adherence counseling (IAC) are offered. IAC is offered to the caregiver or to both the child and the caregiver at one-month intervals by mainly counselors although at times by nurses, clinicians and peer-educators [ 9 ]. After the third session, a post-IAC VL test is done and if suppressed, the patient continues with usual treatment and repeats VL test after a year [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eliminating HIV as a public health threat among adolescents depends heavily on successful implementation of efficacious interventions that address the context in which adolescents live. Across the HIV continuum of care, adolescents are less likely to be tested [4] and linked to care [5], have higher loss to follow-up [6], and worse adherence [7] and viral suppression rates [8] than their adult counterparts despite evidence for appropriate treatment and care [9]. A number of factors, including youth-friendly health services, gender-based violence, harmful cultural and social norms, limit the uptake of health services within this population.…”
Section: Discussion: Adolescent Hiv Implementation Science Alliancementioning
confidence: 99%